Limb Weight Varying Effect on EMG Record of Simple and Discriminative Reaction Time in Elderly Men - Rasool Hemayattalab; Ahmad Nikravan; Fazlolah Bagherzadeh; Mahmood Sheikh (University of Social Welfare & Rehabilitation Sciences, 2014)
Objectives: The effect of variation in contraction force is one of the most important factors in the organization and execution of reaction time (RT) tasks that most of elderly people involved it when they became obese. The present experiment was designed to test the Effect of limb weight varying on pre-motor and motor components of simple and discriminative reaction time in elderly men. Methods & Materials: Subjects (16 old men) were asked to perform forearm flexion to the aim point in 60 cm distance in response to auditory stimulus. The weight of involved limb increased (1.2 Kg) at 50 percent of trials and all trials were measured by electromyogram apparatus. Results: The results of two way repeated measure test showed that the main effects of weight and stimulus on PMT was significant, but the effect of stimulus increasing on MT was not significant (P=0.189). There wasn't any significant interaction effects between limb weight and stimulus increasing on PMT (P=0.888) and MT (P=0.091). Conclusion: These results suggested that the variables that cause to variation in limb inertia can affect RT movement of elderly people.